Specification of concurrently executable modules and distributed modular systems - Weber, H.; Ehrig, H. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
A specification concept for a distributed modular system is introduced. Concurrently executable modules and their interconnections are used as the basis for a computational model for distributed systems that allows the representation of distributed systems in which each of the local subsystems can be concurrently executable. Hence, both internal concurrency within local subsystems and external concurrency in the network between different subsystems can be appropriately expressed. A specification language for systems of that kind, called Pi language is introduced by giving an overview of its syntax and semantics.< >